Answer:
The coordinate of B is (6,0)
Step-by-step explanation:
Given;
coordinate of A = (-4,2) = (x₁, y₁)
coordinate of M = (1,1)
let coordinate of B = (x₂, y₂)
Mid-point is given by;
![M = \frac{X_1 + X_2}{2} , \frac{Y_1 + Y_2}{2}\\\\M= (1,1)\\\\1,1 =\frac{X_1 + X_2}{2} , \frac{Y_1 + Y_2}{2}\\\\ \frac{X_1 + X_2}{2} = 1 ----equation (1)\\\\\frac{Y_1 + Y_2}{2} = 1 -----equation(2)\\\\Solving \ equation(1)\\\\\frac{-4+ X_2}{2} = 1\\\\-4+ X_2 = 2\\\\X_2 = 2+4\\\\X_2 = 6\\\\Solving \ equation(2)\\\\\frac{Y_1 + Y_2}{2} = 1\\\\\frac{2+ Y_2}{2} = 1\\\\2+Y_2 = 2\\\\Y_2 = 2-2\\\\Y_2 = 0\\\\B = (X_2, \ Y_2)\\\\B = (6, \ 0)](https://tex.z-dn.net/?f=M%20%3D%20%5Cfrac%7BX_1%20%2B%20X_2%7D%7B2%7D%20%2C%20%5Cfrac%7BY_1%20%2B%20Y_2%7D%7B2%7D%5C%5C%5C%5CM%3D%20%281%2C1%29%5C%5C%5C%5C1%2C1%20%3D%5Cfrac%7BX_1%20%2B%20X_2%7D%7B2%7D%20%2C%20%5Cfrac%7BY_1%20%2B%20Y_2%7D%7B2%7D%5C%5C%5C%5C%20%5Cfrac%7BX_1%20%2B%20X_2%7D%7B2%7D%20%20%3D%201%20----equation%20%281%29%5C%5C%5C%5C%5Cfrac%7BY_1%20%2B%20Y_2%7D%7B2%7D%20%3D%201%20-----equation%282%29%5C%5C%5C%5CSolving%20%5C%20equation%281%29%5C%5C%5C%5C%5Cfrac%7B-4%2B%20X_2%7D%7B2%7D%20%20%3D%201%5C%5C%5C%5C-4%2B%20X_2%20%3D%202%5C%5C%5C%5CX_2%20%3D%202%2B4%5C%5C%5C%5CX_2%20%3D%206%5C%5C%5C%5CSolving%20%5C%20equation%282%29%5C%5C%5C%5C%5Cfrac%7BY_1%20%2B%20Y_2%7D%7B2%7D%20%3D%201%5C%5C%5C%5C%5Cfrac%7B2%2B%20Y_2%7D%7B2%7D%20%3D%201%5C%5C%5C%5C2%2BY_2%20%3D%202%5C%5C%5C%5CY_2%20%3D%202-2%5C%5C%5C%5CY_2%20%3D%200%5C%5C%5C%5CB%20%3D%20%28X_2%2C%20%5C%20Y_2%29%5C%5C%5C%5CB%20%3D%20%286%2C%20%5C%200%29)
Therefore, the coordinate of B is (6,0)
Circumference is equal to diameter multiplied by pi. C=d X pi. To find the radius we need to rearrange this equation. We know what pi and the circumference are, so to find diameter we do circumference divided by pi. D=c/pi. 942/pi = 299.85. This gives us the diameter, for the radius simply divide by 2 which is 149.92 :)
Answer:
I think it would be C
Step-by-step explanation:
Answer:
( x + 2 ) and ( x - 11 )
Step-by-step explanation:
x² - 9x - 22 = 0
x² + 2x - 11x - 22 = 0
x ( x + 2 ) - 11 ( x + 2 ) = 0
( x + 2 ) ( x - 11 ) = 0
Factors of x² - 9x - 22 are ( x + 2 ) and ( x - 11 ).